2018
DOI: 10.1002/humu.23678
|View full text |Cite
|
Sign up to set email alerts
|

Recessive mutations in the neuronal isoforms of DST , encoding dystonin, lead to abnormal actin cytoskeleton organization and HSAN type VI

Abstract: Hereditary sensory and autonomic neuropathies (HSAN) are clinically and genetically heterogeneous disorders, characterized by a progressive sensory neuropathy often complicated by ulcers and amputations, with variable motor and autonomic involvement. Several pathways have been implicated in the pathogenesis of neuronal degeneration in HSAN, while recent observations point to an emerging role of cytoskeleton organization and function. Here, we report novel biallelic mutations in the DST gene encoding dystonin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
(42 reference statements)
2
28
0
Order By: Relevance
“…We demonstrated that Cre recombination occurs in almost all Schwann cells, but scarcely in sensory neurons using the tdTomato reporter mice (Figure 1). This finding is consistent with previous reports showing selective recombination in Schwann cells, as well as satellite cells, using independent P0-Cre transgenic mice line (Feltri et al, 1999). which is one of the histological hallmarks of neurodegeneration in dt mice (Campbell & Peterson, 1992;Dowling et al, 1997;Horie et al, 2014Horie et al, , 2016Seehusen et al, 2016;Sotelo & Guenet, 1988;Tseng et al, 2006;Tseng et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that Cre recombination occurs in almost all Schwann cells, but scarcely in sensory neurons using the tdTomato reporter mice (Figure 1). This finding is consistent with previous reports showing selective recombination in Schwann cells, as well as satellite cells, using independent P0-Cre transgenic mice line (Feltri et al, 1999). which is one of the histological hallmarks of neurodegeneration in dt mice (Campbell & Peterson, 1992;Dowling et al, 1997;Horie et al, 2014Horie et al, , 2016Seehusen et al, 2016;Sotelo & Guenet, 1988;Tseng et al, 2006;Tseng et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, mutations in plakin genes have also been related with neurological diseases. DST gene mutations result in a hereditary sensory autonomic neuropathy type VI (HSANVI) [204,243,244]. Patients with less dystonin experiment autonomic dysfunction, including cardiovascular dysregulation, altered sweating, and gastrointestinal dysmotility.…”
Section: Mutations In Cytoskeletal Genes Associated With Neurodegenermentioning
confidence: 99%
“…To date, 10 patients have been described with HSAN-VI, 7 of whom continue to live into adulthood and have reported a multitude of autonomic symptoms, including GI problems such as chronic diarrhea and abdominal pain. [1][2][3][4] Furthermore, only one patient has undergone comprehensive GI evaluation, whereby no GI abnormalities could be found that might explain her symptoms. 4 Although it is likely that the root cause of GIT symptoms in HSAN-VI patients is due to autonomic disturbances that are difficult to treat, we may still be able to treat the resulting symp-…”
Section: Discussionmentioning
confidence: 99%
“…1 Since then, at least 7 other cases have been identified in adult individuals presenting with milder symptoms including, joint abnormalities, skin ulcers, hypohidrosis/hyperhidrosis, sexual dysfunction, chronic diarrhea, and abdominal pain. [2][3][4] The variability of symptoms and lifespan between patients can largely be attributed to differences in mutations, and the DST isoforms affected. The most severely affected infant patients possessed a homozygous frameshift mutation that disrupted the expression of all neuronal DST isoforms, 1 while the adult HSAN-VI patients possess mutations that preserve expression of at least one DST isoform.…”
Section: Introductionmentioning
confidence: 99%